Competences in the classroom in the perspectives of foreign language teachers - Consolo, Douglas Altamiro [UNESP] (2013)
In this article we raise some considerations about teachers’ competences, from the perspective of teachers in the Brazilian public sector. The theoretical framework includes articles by Paulo Freire (2001), Philippe Perrenoud (2012), Edgar Morin (2003) and Maurice Tardif (2002) and, based on these authors, we reflect upon issues concerning teachers’ competences taking answers provided by the Brazilian language teachers as a departing point. In a teachers’ course, followed by the same teachers, we posed the main question in our study: Which competences are necessary for a teacher to be considered a good professional at present? From the answers given individually and group discussions we proceeded to a comparative analysis with the adopted framework, and other issues concerning teachers’ competences were considered as well. All the participants mentioned the same two competences, the use of technology and sound knowledge of the course content, and other competences were pointed out by the various teachers as well. Such procedure, besides providing data for our study, also helped as a self-reflexive activity for the teachers involved, about their own professional performance. Given the issues raised in the theoretical texts and the answers provided by the teachers, we expect to revisit the competences necessary for foreign language teacher efficient performance.